2017
DOI: 10.1177/1081286517744600
|View full text |Cite
|
Sign up to set email alerts
|

A semianalytical and finite-element solution to the unbonded contact between a frictionless layer and an FGM-coated half-plane

Abstract: In this work, we examine the receding contact between a homogeneous elastic layer and a half-plane substrate reinforced by a functionally graded coating. The material properties of the coating are allowed to vary exponentially along its thickness. A distributed traction load applied over a finite segment of the layer surface presses the layer and the coated substrate against each other. It is further assumed that the receding contact between the layer and the coated substrate is frictionless. In the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In this work, they were numerically integrated by non-dimensionalizing the integrands, dividing the semi-infinite interval into a larger number of subintervals, separated at the zeros of the sine function, and adding up each pair of neighboring positive and negative contributions. Each of the subintegrals was evaluated with the help of Gauss-Legendre quadrature [44][45][46][47]. To accelerate the convergence, an Euler transformation algorithm was implemented on the resultant alternate series [48].…”
Section: Uniformly Distributed Surface Tractionmentioning
confidence: 99%
“…In this work, they were numerically integrated by non-dimensionalizing the integrands, dividing the semi-infinite interval into a larger number of subintervals, separated at the zeros of the sine function, and adding up each pair of neighboring positive and negative contributions. Each of the subintegrals was evaluated with the help of Gauss-Legendre quadrature [44][45][46][47]. To accelerate the convergence, an Euler transformation algorithm was implemented on the resultant alternate series [48].…”
Section: Uniformly Distributed Surface Tractionmentioning
confidence: 99%
“…The gradation of Young's modulus along the coating thickness was assumed to follow exponential and power law functions. Yan et al 33 studied numerically and analytically the frictionless receding contact problem of an elastic layer and an FGM coated half-plane. In all these studies, good agreement between CHFEs and analytical results was found but the simulations of an FGM component using CHFEs are generally computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…34 Yan et al. 35 considered the frictionless double contact problem involving an FGM coated-homogeneous elastic layer resting on a homogeneous elastic half-plane and indented by a rigid punch. Chidlow and Teodorescu 36,37 derived a semi-analytical model to estimate the stress and displacement fields induced within a layered material including a coating-FGM layer-substrate through frictional contact with another object.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the receding contact problems, El-Borgi and Ç o¨mez 33 studied analytically the receding frictional contact between an FGM layer and a homogeneous half-plane, which were pressed against each other by a rigid stamp. The frictional receding contact problem for two FGM layers pressed by a rigid punch was analyzed using SIE approach and FEM by Yilmaz et al 34 Yan et al 35 considered the frictionless double contact problem involving an FGM coated-homogeneous elastic layer resting on a homogeneous elastic halfplane and indented by a rigid punch. Chidlow and Teodorescu 36,37 derived a semi-analytical model to estimate the stress and displacement fields induced within a layered material including a coating-FGM layer-substrate through frictional contact with another object.…”
Section: Introductionmentioning
confidence: 99%